Fluid modeling and numerical flow specifics in low-permeable gas condensate reservoirs - O. A. Lukin; O. R. Kondrat (Мінеральні ресурси України)
Increasing hydrocarbon production in Ukraine requires development and exploitation of reserves, which are associated with low-permeability gas-saturated reservoirs. There is still no sufficient understanding of the behavior of gas condensate in tight(shale) formations which are characterized by high condensate gas ratio, when the bottom hole pressure is reduced far below the saturation pressure (dew point pressure). Condensate drop out in the reservoir, below the saturation pressure, leads to a major change in the composition of the reservoir gas and liquid, blocking part of the pore space, which significantly reduces the productivity of the wells. The possibilities of determining the quality, composition and impact of condensate dropped out in the reservoir on the productivity of the wells in low-permeability formations are still limited. Also, prediction of the phase behavior of fluids is complicated by the size of pores, that have a nanodimension, where the interaction between fluid and rock at the molecular level can be significant. The effect of condensate ring formation and its impact on the productivity of horizontal wells with multistage hydraulic fracturing operating low-permeable gas condensate reservoirs (0.001–0.1 mD) were investigated using a hydrodynamic simulator of a compositional type. A multi-stage hydraulic fracturing in a synthetic horizontal well was carried out, an equation of state was created on the basis of laboratory report and a compositional hydrodynamic model of the reservoir was built. The results of the simulation showed a significant change in the composition of reservoir fluids and relative permeability of gas in a presence of liquid, with a significant decrease in reservoir pressure, the composition of the dropped out condensate was determined. This allows more detailed and fundamental production forecasting in this type of formations. Also, knowing how fluid composition will change over time with pressure depletion, gives opportunity to calculated minimum miscibility pressure for various EOR agents, during screening and feasibility evaluations.